Editorial Vol.XII - Koirala, Gehendreswor (Economic Literature, 2016)
Editorial board has pleasure to release this issue of Economic Literature, an annual Journal of Department of Economics, Prithvi Narayan Campus, Tribhuvan University, Pokhara (Volume XII, December 2014). Through the publication of this journal. We have been making efforts to promote the general advancement of economic knowledge, information and techniques of analysis since 1981. Our aim is to continue this tradition by publishing highly academic and policy oriented research papers and to provide platforms for enthusiastic scholars who like to publish their scholarly and analytical paper based on fresh research on the issues of interest around the discipline of economics. This issue incorporates analytical articles of contemporary issues of Nepalese economy including deposit mobilization in a commercial bank, government expenditure, multi-dimensional poverty in rural area, impact of remittance, index of human development, financial institution and management practices of graduates. We strongly believe that University Departments should engage in research and disseminate the ideas and findings obtained through research to the scientific community for the enlightenment of knowledge, not just to deliver the existing knowledge in class rooms. We have firmly believed that it will not only enrich field of knowledge but also inspire the fresh graduates towards the culture of scientific research and thoughtful writings. If this publication contributed something to strengthen the culture, we will feel great satisfaction. It is, however, up to the reader to evaluate our endeavour. It was not possible to offer this volume to the esteemed readers without the contributions of the authors of articles included in this issue. We, therefore, reverentially acknowledge the authors who have contributed to the journal. We would also like to thank to those who have assisted us by encouraging the course of this publication. Special thanks go to the campus administration for encouragement and support in various ways. The editorial board welcomes all the noble thoughts, constructive comments and suggestions. Economic Literature Vol.12 2014